2021
DOI: 10.1093/jpe/rtab031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mosaic biological soil crusts on vascular plant establishment in a coastal saline land of the Yellow River Delta, China

Abstract: Aims The effects of biocrusts on vascular plants are rarely evaluated in coastal saline lands. Our aim was to examine whether and how a mosaic of biocrusts affect seed germination of two typical herbaceous plants in a coastal saline land of the Yellow River Delta, to enhance our understanding by which substrate heterogeneity influences plant community dynamics. Methods We conducted growth chamber experiments to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Feng et al 9 , reported that osmotic adjustment can be controlled by biosynthesis of compatible solutes and accumulation/compartmentalization or exclusion of ions. Most plant species, especially halophytes, can maintain the water potential and necessary osmotic gradient for water uptake by accumulating different inorganic ions equal to or more than their concentration in soil solution 49 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Feng et al 9 , reported that osmotic adjustment can be controlled by biosynthesis of compatible solutes and accumulation/compartmentalization or exclusion of ions. Most plant species, especially halophytes, can maintain the water potential and necessary osmotic gradient for water uptake by accumulating different inorganic ions equal to or more than their concentration in soil solution 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have examined the effect of soil salinity on plant yields and growth parameters 8 , 9 which could cause huge losses in plant productivity 10 , 11 . Salt accumulation in soils without suitable vegetation can increase wind erosion and cause the surface sediments to form a sleazy texture 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slama et al (2015) and Delavar et al (2020) mentioned that halophytes can regulate soluble substances like glycine betaine and proline to increase cell volume and maintain osmotic balance under salinity. These organic compounds likely play a role in leaf osmotic adjustment and the protection of membrane stability at severe salinity (Feng et al, 2021). Salt-marsh halophytes cope with salt by excluding entry into roots, sequestering salts intracellular (leading to succulence), and excreting salt via glands, usually on leaf surfaces (Nhu et al, 2020).…”
Section: Some Physiological Aspects Of the Three Halophytic Speciesmentioning
confidence: 99%